Cross metathesis-mediated synthesis of hydroxamic acid derivatives - Chattopadhyay, Shital Kumar; Ghosh, Subhankar; Sil, Suman (Beilstein Journal of Organic Chemistry, 2018)
An alternative synthesis of α,ß-unsaturated hydroxamates via cross metathesis between a class-I olefin and N-benzyloxyacrylamide is reported. The reaction proceeds better in the presence of Grubbs’ second generation catalyst within short time and in good yields (57–85%) with a range of substrates. Subsequent hydrogenation of each of the CM products delivers the title compounds in moderate to very good yield (70–89%). An important demonstration of the protocol is the preparation of the unusual amino acid component of the bioactive cyclic peptide Chap-31.
Keywords: α-amino acid; catalysis; cross metathesis; hydroxamates